Levocarnitine improves cardiac energy metabolic remodeling in myocarditis mice - Yang, Shutong; Li, Xiaoou; Lu, Zhenpeng; Xu, Xiang; Guo, Zuzhen; He, Bing (Frontiers in Pharmacology, 2026)
IntroductionEnergy metabolic remodeling represents a critical pathological mechanism in myocarditis progression. Levocarnitine (LC), an essential cofactor for fatty acid oxidation, demonstrates potential in modulating cardiac metabolism. This study investigated the therapeutic effects of LC on myocardial energy metabolic remodeling and explored the underlying molecular mechanisms.MethodsThe experimental autoimmune myocarditis (EAM) mouse model was constructed using α-myosin. Cardiac function, myocardial inflammatory infiltration, and mitochondrial structure were evaluated using echocardiography, HE staining, and transmission electron microscopy, respectively. Metabolic parameters including free fatty acid (FFA), lactic acid (LAC), mitochondrial complex IV (COX IV) activity, and adenosine triphosphate (ATP) levels were measured using colorimetry. Serum heart-type fatty acid-binding protein (H-FABP) levels were measured by ELISA, and reactive oxygen species (ROS) levels were determined by flow cytometry. The expression of organic carnitine transporter type 2 (OCTN-2) and carnitine palmitoyltransferase-1B (CPT-1B) were determined by Western blot. Furthermore, network pharmacology and molecular docking were employed to predict the therapeutic targets and mechanisms of LC in myocarditis. The activity of the phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) pathway and the expression of peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α) were verified by Western blot.ResultsLC treatment significantly improved cardiac function and attenuated myocardial inflammatory infiltration in EAM mice. It ameliorated mitochondrial structural damage, enhanced COX IV activity and ATP production, and reduced the accumulation of FFA, LAC and ROS in myocardial tissues. It also lowered serum H-FABP levels while upregulating the expression of OCTN-2 and CPT-1B. Combining network pharmacology and molecular docking, Akt was identified as the key therapeutic target of LC in cardiomyopathy and demonstrated good binding affinity with LC. In vivo validation confirmed that LC decreased Akt phosphorylation in the myocardium of EAM mice, while PGC-1α expression increased.ConclusionLC effectively improved myocardial metabolic remodeling and alleviated cardiac insufficiency in myocarditis. The underlying mechanism may involve LC-mediated suppression of the PI3K/Akt signaling pathway, potentially linked to increased expression of the key mitochondrial regulator PGC-1α.